Socio-economic Factors Affecting Residential Land Accessibility in Akure Nigeria: A Gender Perspective (International Journal of Built Environment and Sustainability, 2017)
Land defines the social, economic and political relations in the society and is the most crucial factor of production. Access to land promotes the economic power of individuals and their contribution to the economy of the nation at large. It is both a resource and a focal point of social identity and solidarity. This paper is aimed at revealing the sources of gaining access to residential land in Akure by both male and female home owners with a view to engendering appropriate policy response towards female housing ownership. The sample size was determined from the 2006 population census figure of the Akure South Local Government Area. A total of three hundred and eighty one (381) questionnaires were administered to home-owners using systematic and stratified random sampling techniques and were found useful for analysis. The means of gaining access to residential land in the selected towns in the study area include purchase, inheritance, government allocation and gift. Discriminant Function Analysis was used to determine which socio-economic variables were the best predictors of how access to land can be gained. Occupation, income and education emerged as the best predictors out of all the socio-economic variables used. The paper recommends the provision of enabling environment to boost informal employment which is predominant in the study area as this will increase the income level of the citizens. There is also the need for public enlightenment on how to access land through government allocation which was very low in the study area.